2020
DOI: 10.3389/fphys.2020.00391
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Faba Beans (Vicia faba L.) Reduces Myocyte Metabolic Activity in Grass Carp (Ctenopharyngodon idellus)

Abstract: In this study, we aimed to explore the effects of faba bean (Vicia faba L.) on the energy metabolism of grass carp (Ctenopharyngodon idellus). A total of 180 fish (∼2900 g) were randomly assigned to six tanks (2.5 × 2.5 × 1.2 m; 30 individuals per tank) and fed either faba bean (Vicia faba L.) or a commercial diet for 120 days (3% body weight, twice per day). The results showed that faba bean-fed grass carp (FBFG) had significantly lower growth and higher fat accumulation in the mesenteric adipose tissue and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…Reducing lipid accumulation using creatine in GC is consistent with the response in mammals [6,28]. A previous study showed that fat accumulation increased when tissue creatine decreased in GC upon faba bean consumption [29], suggesting a negative correlation between fat accumulation and creatine. However, our results are not consistent with the red drum carnivorous fish [12,13].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Reducing lipid accumulation using creatine in GC is consistent with the response in mammals [6,28]. A previous study showed that fat accumulation increased when tissue creatine decreased in GC upon faba bean consumption [29], suggesting a negative correlation between fat accumulation and creatine. However, our results are not consistent with the red drum carnivorous fish [12,13].…”
Section: Discussionsupporting
confidence: 78%
“…Third, it is known that the end product of β-oxidation, acetyl-CoA forms NADPH and FADH 2 , as part of the tricarboxylic acid cycle. Moreover, NADPH and FADH 2 then enter the mitochondrial respiratory chain, whereby with the help of five enzymatic complexes ATP is produced [29]. Our in vivo study showed that the protein concentrations of complexes I-V were all increased after the fish were fed creatine, and the in vitro study showed that appropriate concentrations of creatine increased the relative transcript levels of several genes in complexes I-III.…”
Section: Discussionmentioning
confidence: 57%
“…Free fatty acids released through lipolysis or autophagy/lipophagy are transported to the mitochondria for β-oxidation by a series of enzymes to produce acetyl-CoA as the end product [ 18 ]. Acetyl-CoA then enters the tricarboxylic acid cycle to form NADPH and FADH2, which are absorbed by the mitochondrial respiratory chain, through which five enzymatic complexes produce ATP [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, MAS caused by A. hydrophila has hindered the rapid development of carp industry in China and catfish industry in the United States ( 4 , 5 ). Grass carp ( Ctenopharyngodon idellus ) is the fish species with the most significant reported production in aquaculture globally, with a proportion of up to 5.5 million tons per year ( 6 ). Increased incidence of infection and the broad spectrum of antibiotic resistance has made A. hydrophila a severe threat to the aquaculture industry.…”
Section: Introductionmentioning
confidence: 99%